Hydrogels of copolymers of beta-vinyloxyethylamide of acrylic acid with unsaturated carboxylic acids - Burkeev, M. Zh.; Tazhbaev, E. M.; Kazhmuratova, A. T.; Sugralina, L. M.; Zhaparova, L. Zh. (Springer, 2007)
The effect of external factors on the behavior of hydrogels based on copolymers of β-vinyloxyethylamide of acrylic acid with acrylic and methacrylic acids was studied. The response of hydrogels to changes in the pH of medium, the concentration of low-molecular-mass salts, and solvent quality was experimentally shown.